1995
DOI: 10.1159/000168793
|View full text |Cite
|
Sign up to set email alerts
|

An Outbreak of Gram-Negative Bloodstream Infections in Chronic Hemodialysis Patients

Abstract: Six chronic hemodialysis patients acquired bloodstream infections (BSIs) with Klebsiella pneumoniae of the same serotype and similar plasmid profile during an 11-day period. The 6 case-patients were more likely than noncase-patients to have received dialysis during the fourth shift (p < 0.05) and to have their dialyzers reprocessed for reuse after those of the noncase-patients (p = 0.05). Investigation identified a patient during the same shift with an arteriovenous fistula infected with K pneumoniae. The dial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(28 citation statements)
references
References 6 publications
0
28
0
Order By: Relevance
“…Most BSI outbreaks in hemodialysis units have resulted from inadequate disinfection of water treatment and distribution systems, reprocessed dialyzers, or other dialysis equipment [3][4][5][6][7][8][9][10]. During this outbreak, 12 patients were identified with E. cloacae BSI or PR.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most BSI outbreaks in hemodialysis units have resulted from inadequate disinfection of water treatment and distribution systems, reprocessed dialyzers, or other dialysis equipment [3][4][5][6][7][8][9][10]. During this outbreak, 12 patients were identified with E. cloacae BSI or PR.…”
Section: Discussionmentioning
confidence: 99%
“…The procedure remains potentially hazardous to patients, and numerous clusters of gram-negative bacteremia and pyrogenic reactions (PR) have been reported. Most such clusters have been traced to bacterial contamination of water and/or dialysate [3,4], errors in dialyzer reprocessing [5][6][7], and improper setup procedures [8][9][10]. In this paper, we describe an outbreak of Enterobacter cloacae bloodstream infections and PR at Hôpital Charles-LeMoyne, a 590-bed university-affiliated teaching hospital in the Montreal area, that was first detected in August 1995 when five episodes of bacteremia occurred among the dialysis unit's 60 chronic hemodialysis patients.…”
Section: Introductionmentioning
confidence: 99%
“…In our study, Ames test showed that different generations of PAMAM (G2, G3, G4 and G5) had mutagenicity effects and reverted colonies were increased by higher-generation of PAMAM dendrimers. The Ames test has specific features such as sensitivity and specificity; so different materials can be used in this test (30). Pounikar and Dawande using the Ames test showed that ethidium bromide, sodium aside, hair dye, colors and food additives had mutagenic response on auxotrophic strain (his-) and induced reversion mutation (his+).…”
Section: Discussionmentioning
confidence: 99%
“…cultured using calibrated loop and blood agar plates-results were always recorded as no growth Phialemonium curvatum access infections Observations at the facility noted some irregularities Review infection control practices; clean and disinfect in 4 hemodialysis patients; 2 of these in site prep for needle insertion. All 156 of headers with gauze; staff not routinely header; change gloves frequently; process dialyzers changing gloves; dialyzers not processed for immediately after rinsing and cleaning several hours after disassembly and cleaning Pyrogenic reactions in 3 high-flux dialysis patients 157 Dialyzer reprocessed with two disinfectants; water Do not disinfect dialyzers with multiple germicides; more used for reuse did not meet AAMI standards frequent disinfection of water system Pyrogenic reactions in 14 high-flux dialysis Dialyzers rinsed with city water; water for reuse Do not rinse or clean dialyzers with city water; disinfect patients; 1 death 158 did not meet AAMI standards water treatment system more frequently Pyrogenic reactions in 18 patients 51 Dialyzers rinsed with city water containing high Do not rinse or clean dialyzers with city water; disinfect levels of endotoxin; water used for reuse did not water treatment system more frequently meet AAMI standards Pyrogenic reactions in 22 patients 159 Water for reuse did not meet AAMI standards; Use correct microbial assay procedure; disinfect water improper microbial assay technique distribution system…”
Section: High-flux Dialysis and Bicarbonate Dialysatementioning
confidence: 99%